Long-term outcomes after perioperative treatment with omega-3 fatty acid supplements in colorectal cancer. Issue 4 (11th May 2020) - Sørensen, L Schmidt; Rasmussen, S Ladefoged; Calder, P C; Yilmaz, M Nytoft; Schmidt, E Berg; Thorlacius-Ussing, O
Abstract: Background: This study aimed to evaluate the effect of perioperative supplementation with omega-3 fatty acids ( n -3 FA) on perioperative outcomes and survival in patients undergoing colorectal cancer surgery. Methods: Patients scheduled for elective resection of colorectal cancer between 2007 and 2010 were randomized to either an n -3 FA-enriched oral nutrition supplement (ONS) twice daily or a standard ONS (control) for 7 days before and after surgery. Outcome measures, including postoperative complications, 3-year cumulative incidence of local or metastatic colorectal cancer recurrence and 5-year overall survival, were compared between the groups. Results: Of 148 patients enrolled in the study, 125 (65 patients receiving n -3 FA-enriched ONS and 60 receiving standard ONS) were analysed. There were no differences in postoperative complications after surgery ( P = 0·544). The risk of disease recurrence at 3 years was similar (relative risk 1·66, 95 per cent c.i. 0·65 to 4·26). The 5-year survival rate of patients treated with n -3 FA was 69·2 (95 per cent c.i. 56·5 to 78·9) per cent, compared with 81·7 (69·3 to 89·4) per cent in the control group ( P = 0·193). After adjustment for age, stage of disease and adjuvant chemotherapy, n -3 FA was associated with higher mortality compared with controls (hazard ratio 1·73, 95 per cent c.i. 1·06 to 2·83; P = 0·029). The interaction between n -3 FA and adjuvant chemotherapy was not statistically significant. Conclusion: Perioperative supplementation with n -3 FA did not confer a survival benefit in patients undergoing colorectal cancer surgery. n -3 FA did not benefit the subgroup of patients treated with adjuvant chemotherapy or decrease the risk of disease recurrence. Graphical Abstract: Perioperative treatment with omega-3 fatty acids ( n -3 FA) does not confer an overall survival benefit in patients undergoing colorectal cancer surgery, and neither is it associated with an increased efficacy of adjuvant chemotherapy. Clinicians should be careful when making any recommendations regarding the use of n -3 FA oral nutritional supplements, as the effects are not thoroughly established. Fatty acids supplements and colon cancer